The Periodic Table of Elements and Other Materials… for the Final Chemistry Exam; Students’ Opinion - Krzeczkowska, Małgorzata (Annales Universitatis Paedagogicae Cracoviensis. Studia ad Didacticam Scientiarum Socialium Pertinentia, 2020)
All school chemistry teachers, along with their students, realize that the periodic table of elements (and some other reference literature chemistry materials) is one of the most fundamental sources of information in chemistry. School and university students were surveyed in order to collect their opinions on the frequency of use of these materials in the class, together with their judgement on which elements were used. I would also like to know: Do teachers at school teach how to use the reference literature chemistry materials?